Pengaruh Profitabilitas terhadap Penghindaran Pajak dengan Komite Audit sebagai Variabel Moderasi - Vina Asprilla; Priyo Hari Adi (Owner : Riset dan Jurnal Akuntansi, 2023)
This study was conducted to examine the effect of profitability on tax avoidance with the audit committee as a moderating variable. Tax avoidance as the dependent variable measured using the effective tax rate (ETR), profitability as an independent variable measured using return on assets (ROA), audit committee as a moderating variable measured using the number of audit committees of companies listed on the Indonesia Stock Exchange (IDX), and inventory intensity as a measurable control variable by comparing total inventory with total assets. This research was conducted at food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for a period of 5 years, namely 2017 to 2021. The sample used a purposive sampling technique so that there were 16 companies that matched the comparison and obtained 80 observational data. The data used in this study is secondary data in the form of financial statements of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) which can be downloaded via www.idx.co.id. Data analysis techniques using multiple linear regression analysis and moderate regression analysis (MRA) and is processed using SPSS 21 version program. The results showed that profitability had a significant positive effect on tax evasion and the audit committee was not able to moderate the relationship between profitability and tax evasion.